Anti-leptospirosis agglutinins in Brazilian capybaras (hydrochoerus hydrochaeris). Issue 1 (December 2016) - Langoni, Helio; Kuribara, Ivone; Ferreira Lopes Correa, Ana; Ullmann, Leila; Sánchez, Gabriela; Lucheis, Simone
Abstract Background The interest in commercial use of wild animals is increasing, especially regarding raising of capybaras. Although this wild species is potentially lucrative for the production of meat, oil and leather, it is suggested as a probable reservoir of leptospires. Methods Due to the economic importance of this species and the lack of studies concerning leptospirosis, the presence of anti-leptospirosis agglutinins was assayed in 55 serum samples of capybaras (Hydrochoerus hydrochaeris ) from commercial and experimental breeding flocks located in São Paulo state, Paraná state, and Rio Grande do Sul state, Brazil. Samples were obtained through cephalic or femoral venipunction (5 to 10 mL). Microscopic agglutination test was used according to the Brazilian Health Ministry considering as cut-off titer of 100. Results Out of the 55 samples analyzed, 23 (41.82 %) tested positive. The most prevalent serovar was Icterohaemorrhagiae (56.52 %) in 13 samples, followed by Copenhageni in nine samples (39.13 %), Pomona in four samples (17.39 %), Djasiman and Castellonis in three samples each (13.04 %), Grippotyphosa, Hardjo, Canicola, and Cynopteri in two samples each (8.7 %), and Andamana and Bratislava in one sample each (4.34 %). Conclusions These results suggest the evidence of exposure toLeptospira spp. and the need of new studies to evaluate a higher number of capybaras from different regions to better understand the importance of leptospirosis infection in these animals and verify the zoonotic role of this species as a possible source of infection to humans and other animals.